DOP01 Efficacy and safety of the IL-6 trans-signalling inhibitor olamkicept: a phase 2 randomized, placebo-controlled trial in moderately to severely active Ulcerative Colitis. (27th May 2021) - Chen, B; Zhang, S; Wang, B; Chen, H; Li, Y; Cao, Q; Zhong, J; Xie, M; Ran, Z; Tang, T; Yang, M; Guo, T; et al.
Abstract: Background: Total inhibition of IL-6 or its receptor represents a potent anti-inflammatory therapy with considerable side effects. Selective targeting IL-6 trans-signalling may have safety advantages that differentiates it from current pan-IL-6 inhibitors. We evaluated the efficacy and safety of olamkicept, a soluble gp130-Fc fusion protein that binds to the IL-6 and soluble IL-6 receptor complex, as induction therapy for active ulcerative colitis (UC). Methods: This multi-national, randomized, double-blind, placebo-controlled phase 2 trial (NCT03235752) enrolled patients with active UC (full Mayo score ≥5, rectal bleeding (RB) score ≥1, endoscopy score (ES) ≥2) with an inadequate response to at least conventional therapy, in a 1:1:1 ratio to receive either placebo, olamkicept 300 mg or 600 mg biweekly for 12 weeks. Primary efficacy endpoint was clinical response (decrease in Mayo score from baseline ≥3 and ≥30%, including RB ≤1 or RB decrease ≥1) at week 12. Secondary endpoints were mucosal healing (ES 0 or 1) and clinical remission (Mayo score ≤2, with no subscore >1 and RB=0). The efficacy endpoints were analysed by logistic regression. All p-values were 2-sided without adjustment for multiplicity. Results: Of 91 treated patients (30 in placebo, 31 in olamkicept 300 mg group and 30 in 600 mg group), 88 patients (29:30:29) were evaluable for efficacy. Baseline disease and demographic characteristics were similar among the groups (Table 1). Most patients (94.5%) were bio-naïve. The percentage of patients achieving clinical response at week 12 was significantly greater for olamkicept 600 mg than placebo (58.6% vs 34.5%, P=0.032). Clinical remission at week 12 occurred in 0% (placebo), 6.7% (olamkicept 300 mg) and 20.7% (olamkicept 600 mg, P<0.001) of patients. Mucosal healing at week 12 occurred in 3.4%, 10% and 34.5% (P<0.001) of patients, respectively (Figure 1). Incidence of treatment emergent adverse events (TEAEs) was similar across the groups. The most common TEAEs included upper respiratory tract infection, increased AST levels, and increased urine bilirubin levels, which were mild to moderate and mostly transient. Serious adverse events (SAEs) were reported in 6.7%, 3.2% and 3.3% of patients, respectively. There were no deaths, or other severe AEs associated with current IL-6 inhibitors, such as perforations, severe infections, neutropenia or thrombocytopenia. Conclusion: Biweekly 600 mg olamkicept induction therapy demonstrated clinical efficacy with respect to achieving clinical response, clinical remission and mucosal healing in patients with active UC. Olamkicept was well tolerated with a favourable safety profile. The positive results of this phase 2 study support further development of olamkicept in IBD.